2018
DOI: 10.1037/ser0000209
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric symptom severity, criminal risk, and suicidal ideation and attempts among not guilty by reason of insanity state hospital inpatients.

Abstract: Individuals forensically committed to a state hospital are at an increased risk of suicide; however, there is extremely limited research examining suicide risk estimates and risk factors among inpatients deemed not guilty by reason of insanity (NGRI). This study aimed to determine (a) rates of suicidal ideation history, suicide attempt history, and current distress due to suicidal ideation, and (b) the associations between psychiatric symptom severity, criminal risk factors, and suicide risk. NGRI inpatients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Therefore, categorical data analysis methods were used, which allowed us to provide clinically useful estimated probabilities. The BSI Item 9 has also been used as a categorical criterion variable in previous research and has been associated with suicide risk factors (i.e., Jahn et al, 2018; Mitchell et al, 2018; Mitchell et al, 2017). Previous research has also indicated that TB and PB were significantly associated with both suicide ideation distress and suicide ideation (Mitchell et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, categorical data analysis methods were used, which allowed us to provide clinically useful estimated probabilities. The BSI Item 9 has also been used as a categorical criterion variable in previous research and has been associated with suicide risk factors (i.e., Jahn et al, 2018; Mitchell et al, 2018; Mitchell et al, 2017). Previous research has also indicated that TB and PB were significantly associated with both suicide ideation distress and suicide ideation (Mitchell et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Mitchell et al (2018) note that very little research exists on suicidal ideation (SI) in this population. In their study, 58% of acquittees experienced SI, which was statistically associated with psychiatric symptoms but not criminal tendencies.…”
Section: Resultsmentioning
confidence: 99%
“…It was more likely, however, for acquittees with high criminal tendencies and low antisocial traits to experience SI than those with moderate to high antisocial traits, perhaps mediated by feelings of guilt, shame, or loss that are less pronounced in those with more antisocial features. Therefore, these authors recommend addressing both psychiatric symptoms and criminogenic risk in treatment planning (Mitchell et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study indicated a suicide rate of 101 suicides per 100,000 psychiatric hospital admissions among inpatients during hospitalization (Neuner et al, 2008). A recent study among inpatients found NGRI indicated that approximately 46% reported at least one previous suicide attempt, 58% reported previous suicidal thoughts, and 10% reported current suicide ideation distress (Mitchell et al, 2018a). Furthermore, the severity of psychiatric symptoms was associated with greater suicide ideation distress and suicide attempt history (Mitchell et al, 2018a).…”
mentioning
confidence: 99%